BK Polyomavirus-specific T cell immune responses in kidney transplant recipients diagnosed with BK Polyomavirus-associated nephropathy - Jackrapong Bruminhent (2020)
© 2019 The Author(s). Background: Adjustment of immunosuppression is the main therapy for BK polyomavirus (BKPyV)-associated nephropathy (BKPyVAN) after kidney transplantation (KT). Studies of BKPyV-specific T cell immune response are scarce. Here, we investigated BKPyV-specific T cell immunity in KT recipients diagnosed with BKPyVAN. Methods: All adult KT recipients with BKPyVAN diagnosed at our institution from January 2017 to April 2018 were included. Laboratory-developed intracellular cytokine assays measuring the percentage of IFN-γ-producing CD4+ and CD8+ T cells, after stimulation with large-T antigen (LT) and viral capsid protein 1 (VP1), were performed both at the time of diagnosis and after adjustment of immunosuppression. Results: We included 12 KT recipients diagnosed with BKPyVAN (7 proven, 4 presumptive, and 1 possible). Those with presumptive BKPyVAN had a median plasma BKPyV DNA load of 5.9 log10 copies/ml (interquartile range [IQR]: 4.9-6.1). Adjusted dosing of mycophenolic acid and tacrolimus with (86%) or without (14%) adjunctive therapies were implemented after diagnosis. There was a significantly higher median percentage of IFN-γ-producing CD4+ T cells to LT at a median of 3 (IQR: 1-4) months after adjustment of immunosuppression compared with at the time of diagnosis (0.004 vs. 0.015; p = 0.047). However, the difference between the median percentage of IFN-γ-producing CD4+ T cells to VP1 and CD8+ T cells to LT and VP1 did not reach statistical significance. Four (33%) patients achieved plasma BKPyV DNA clearance, and the remaining eight (67%) patients had persistent BKPyV DNAemia. Although eight (67%) patients developed allograft dysfunction, none required hemodialysis. Conclusions: We observed a marginal trend of BKPyV-specific CD4+ T cell recovery after adjustment of immunosuppression in KT recipients diagnosed with BKPyVAN. A further study would be benefited to confirm and better assess BKPyV-specific immune response after KT.